Department of Information Technology in Institute of Medicine - Vaidya, P (Journal of Institute of Medicine Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Journal of Institute of Medicine, August, 2008; 30:2 1 The full text of this paper is available from the Journal of Institute of Medicine website